Catalog it! a guide to cataloging school library materials - Kaplan, Allison G.; Riedling, Ann Marlow 1952- (Gale virtual reference library, 2006)
Contains expanded information on Library of Congress Subject Headings and electronic cataloging and cataloging systems, as well as Dewey Decimal Classification (DDC) and Machine Readable Cataloging (MARC).